La historia en los libros de texto de física y química para secundaria: las diferentes formas de presentar la información histórica y las opiniones relacionadas de los alumnos - D Méndez.; Slisko, J. (Revista Mexicana de Física E, 2014)
This article presents the historical information that appears in Spanish Physics and Chemistry textbooks for 14 and 15-year-old students, it focuses on the purpose of the authors when they use this kind of information. Moreover, it has done a 17 questions survey to 69 students of these ages in order to show if the historical aspects that appear in Physics and Chemistry textbooks are useful or not. Some of the students affirm that it is helpful because this information contextualizes Physics, that is useful to understand and remember it better. However, other students declare that history is boring and is not of a great help in Physics learning.